2014
DOI: 10.1111/hcre.12030
|View full text |Cite
|
Sign up to set email alerts
|

Proactive vs. Retroactive Mediation: Effects of Mediation's Timing on Children's Reactions to Popular Cartoon Violence

Abstract: An experiment with 150 children aged 5–7 and 10–12 revealed that children's reactions to violent TV shows differed based on when they received negatively valenced, evaluative mediation. Results also showed that the effect of mediation's timing consistently depended on children's age. Older children responded better to pre‐exposure mediation than they did to postexposure mediation. In some cases, older children exhibited reactance to postexposure mediation. For younger children, on the other hand, mediation giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…However, it is particularly notable that active mediation styles also did not moderate the relationship between media violence and aggression in the concurrent analyses, even though the cross-sectional correlations between active mediation styles, media use, and aggressive behavior in this study (see Table 1) were in line with those found in a recent meta-analysis (Collier et al, 2016). While several studies have shown that active mediation can influence children's knowledge about or attitudes toward violent television content (e.g., Linder & Werner, 2012;Nathanson & Yang, 2003;Nathanson, 2004;Rasmussen, 2014), our findings e in combination with the inconsistent active mediation findings from previous research (Grusec, 1973;Hicks, 1968;Mattern & Lindholm, 1985;Nathanson & Cantor, 2000;Nathanson, 1999Nathanson, , 2004 e raise questions about the effectiveness of active mediation as a strategy to reduce the potential effects of media violence exposure on aggressive behavior. Given the persuasive theoretical argumentation underlying active mediation (Cantor & Wilson, 2003), it is somewhat surprising that we do not find similarly persuasive empirical evidence for active mediation as a strategy to reduce the relationship between media violence and aggression.…”
Section: Active Mediation Stylessupporting
confidence: 78%
See 1 more Smart Citation
“…However, it is particularly notable that active mediation styles also did not moderate the relationship between media violence and aggression in the concurrent analyses, even though the cross-sectional correlations between active mediation styles, media use, and aggressive behavior in this study (see Table 1) were in line with those found in a recent meta-analysis (Collier et al, 2016). While several studies have shown that active mediation can influence children's knowledge about or attitudes toward violent television content (e.g., Linder & Werner, 2012;Nathanson & Yang, 2003;Nathanson, 2004;Rasmussen, 2014), our findings e in combination with the inconsistent active mediation findings from previous research (Grusec, 1973;Hicks, 1968;Mattern & Lindholm, 1985;Nathanson & Cantor, 2000;Nathanson, 1999Nathanson, , 2004 e raise questions about the effectiveness of active mediation as a strategy to reduce the potential effects of media violence exposure on aggressive behavior. Given the persuasive theoretical argumentation underlying active mediation (Cantor & Wilson, 2003), it is somewhat surprising that we do not find similarly persuasive empirical evidence for active mediation as a strategy to reduce the relationship between media violence and aggression.…”
Section: Active Mediation Stylessupporting
confidence: 78%
“…Although several studies have shown that active mediation can indeed change children's perceptions of media violence (e.g., Nathanson & Cantor, 2000;Nathanson, 2004;Rasmussen, 2014), the evidence for a subsequent reduction in aggression is less consistent. Nathanson's (1999) cross-sectional survey reports a negative relationship between active mediation and children's general aggressive tendencies.…”
Section: Parental Mediation Media Violence and Aggressionmentioning
confidence: 98%
“…However, it may also be worthwhile to study the role of parent's modeling of violent behavior (i.e., being aggressive themselves), co-use of violent media (i.e., using violent media together), and positive mediation (i.e., endorsing violent content). Also, it may be valuable to examine the timing of mediation, as a recent experimental study suggest that mediation is most effective when it is done before or during media exposure, as opposed to mediation after exposure (Rasmussen, 2014). Another particularly fruitful area of investigation is the role of peers.…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…Parental mediation can moderate the relationship between media violence exposure and normative beliefs about aggression, i.e., for children with less parental mediation, predictability of violent media exposure on normative beliefs about aggression is stronger (Linder and Werner, 2012). Parental mediation is closely linked to decreased aggression caused by violent media (Nathanson, 1999; Rasmussen, 2014; Padilla-Walker et al., 2016). Further studies have shown that the autonomy-supportive restrictive mediation of parents is related to a reduction in current aggressive behavior by decreasing media violence exposure; conversely, inconsistent restrictive mediation is associated with an increase of current aggressive behavior by enhancing media violence exposure (Fikkers et al., 2017).…”
Section: Introductionmentioning
confidence: 99%